A Statistical Analysis of Banking Performance in the Eastern Caribbean Currency Union in the 1990s - Juan-Ramon, V.; Randall, Ruby.; Williams, Oral. (Washington, D.C. : International Monetary Fund, 2001)
Private foreign banks dominate the banking system although their market share declined in the 1990s while that of private indigenous banks increased. The banking system was not concentrated either within or across countries. Stigler's survivor test indicated that large banks tended to reduce their scale over time. Private foreign and private indigenous banks exhibited similar distributions with respect to operating expenses but private foreign banks were most profitable. High interest rate spreads appeared attributable to higher average costs related to market size and geographic peculiarities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet